1996
DOI: 10.1038/bjc.1996.357
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacological and anti-tumour effects of the specific anti-oestrogen ICI 182780 in women with advanced breast cancer

Abstract: Summary We have assessed the pharmacokinetics, pharmacological and anti-tumour effects of the specific steroidal anti-oestrogen ICI 182780 in 19 patients with advanced breast cancer resistant to tamoxifen. The agent was administered as a monthly depot intramuscular injection. Peak levels of ICI 182780 occurred a median of 8-9 days after dosing and then declined but were above the projected therapeutic threshold at day 28. Cmax during the first month was 10.5 ng/ml-' and during the sixth month was 12.6 ng ml-l.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
86
0
10

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(100 citation statements)
references
References 32 publications
(12 reference statements)
4
86
0
10
Order By: Relevance
“…15,16 The pure antiestrogen ICI 182,780 (ICI), however, has been reported to be effective even in patients with hormone-independent breast cancer. 17 Several mechanisms for antiestrogen action have been proposed, including the inhibition of c-myc gene expression, 12,13 downregulation of the estrogen receptor (ER), impairment of ER dimerization and ER shuttling. 15,16 In addition, ICI attenuated the cells' response to growth factors, however, it is unclear if these effects are dependent upon ER function.…”
mentioning
confidence: 99%
“…15,16 The pure antiestrogen ICI 182,780 (ICI), however, has been reported to be effective even in patients with hormone-independent breast cancer. 17 Several mechanisms for antiestrogen action have been proposed, including the inhibition of c-myc gene expression, 12,13 downregulation of the estrogen receptor (ER), impairment of ER dimerization and ER shuttling. 15,16 In addition, ICI attenuated the cells' response to growth factors, however, it is unclear if these effects are dependent upon ER function.…”
mentioning
confidence: 99%
“…Moreover, magnetic resonance imaging of the uterus in ovarectomised monkeys also suggests that fulvestrant is an effective antioestrogen (Dukes et al, 1992(Dukes et al, , 1993. The data surrounding the clinical potential of fulvestrant in postmenopausal patients with breast cancer have been encouraging (Defriend et al, 1994;Howell et al, 1996Howell et al, , 2002Osborne et al, 2002). In this group of patients, fulvestrant inhibits tumour cell proliferation associated with a profound decrease in immunocytochemically detectable ER protein (Defriend et al, 1994;Robertson et al, 2001).…”
mentioning
confidence: 99%
“…In this group of patients, fulvestrant inhibits tumour cell proliferation associated with a profound decrease in immunocytochemically detectable ER protein (Defriend et al, 1994;Robertson et al, 2001). One small phase II trial, involving 19 postmenopausal patients with tamoxifen refractory disease, suggested that fulvestrant might have fewer side effects in terms of menopausal symptoms than tamoxifen, with no negative effects being observed on the liver, brain or genital tract (Howell et al, 1996). The pharmacokinetic data associated with these studies in breast cancer patients showed that monthly intramuscular (i.m.)…”
mentioning
confidence: 99%
See 2 more Smart Citations